Seeing the Forest for the Trees: The Future of Timber Investing in the North Woods -- A Conversation with Clark S. Binkley - Howell, Peter (Maine Policy Review, 2007)
In this conversation with Peter Howell, Clark Binkley draws on his long-term experience as a timberland investment manager to give his analysis of and forecast for timber markets and timber investing in the Northern Forest. While he is not optimistic about the current prospects for such investments, he does believe that there are some opportunities in conservation easements, residential development, and possibly biofuels and carbon credits.
Keywords: Maine North Woods; timber industry; forestry economics